Diurnal pattern of respiration in corals and algae and its implications for gross primary production quantification - Yvonne Sawall; Roderick Bakker; Natalia E. Padillo-Anthemides; Nicole Adamson (PLoS ONE, 2025)
Mitochondrial respiration (R) and gross photosynthesis (GP) are crucial components of the energy and carbon budgets of photosynthesizing organisms in coral reefs. This study investigates the diurnal and seasonal patterns of R in common reef algae and corals, examining the relationship between R and photosynthesis. Additionally, it evaluates discrepancies between daily R and GP calculations based on diurnal variations versus constant nighttime R, latter being the more traditional approach. We collected three coral species (Montastrea cavernosa, Porites astreoides, and Diploria strigosa) and three algal species (Caulerpa verticillata, Ceramium nitens, and Laurencia obtusa) from a Bermuda reef in fall (October) and measured their metabolic rates in a controlled outdoor mesocosm environment. Diurnal patterns of photosynthesis were measured under natural sunlight, and respiration was measured at different times by covering the incubations with a black sheet. Measurements were repeated with re-collected corals in spring (April) and summer (July). Our findings reveal pronounced diurnal patterns in R for both corals and algae, with peak R in the afternoon, lagging behind peak GP by 1–3 hours. Seasonal analysis showed the highest R in summer and the lowest in fall, correlating with temperature and light intensity variations. The study indicates that traditional models, assuming constant nighttime R throughout the day, underestimate daily R and GP rates by an average of 14% and 13%, respectively, and by 23% and 18% at a maximum. These results highlight the need to incorporate the dynamic nature of respiration into our understanding of energy and carbon fluxes in reef organisms. As metabolic energy availability is crucial for organism resilience, improved estimates of R and GP are essential for predicting organism survival in a changing environment.